1997
DOI: 10.1152/ajpregu.1997.273.3.r864
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide within the paraventricular nucleus mediates changes in renal sympathetic nerve activity

Abstract: The paraventricular nucleus (PVN) of the hypothalamus is known to be involved in the control of sympathetic outflow. The goal of the present study was to examine the role of nitric oxide within the PVN in the regulation of renal sympathetic nerve activity. Renal sympathetic nerve discharge (RSND), arterial blood pressure, and heart rate in response to the microinjection of nitric oxide synthase inhibitor NG-monomethyl-L-arginine (L-NMMA; 50, 100, and 200 pmol) into the PVN were measured in male Sprague-Dawley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
160
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(177 citation statements)
references
References 0 publications
12
160
1
1
Order By: Relevance
“…We observed that microinjection of an inhibitor of NOS, N G -monomethyl-L-arginine (L-NMMA), increased RSND, arterial blood pressure, and heart rate (19). These data indicate that the endogenous NO system within the PVN is involved in mediating sympathetic outflow.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…We observed that microinjection of an inhibitor of NOS, N G -monomethyl-L-arginine (L-NMMA), increased RSND, arterial blood pressure, and heart rate (19). These data indicate that the endogenous NO system within the PVN is involved in mediating sympathetic outflow.…”
mentioning
confidence: 85%
“…Localization of neuronal populations that possess neuronal NOS (nNOS) has been achieved by histochemical staining using NADPH-diaphorase and immunohistochemistry (1,5). This close proximity of the production of NO within central sites that are involved in cardiovascular regulation have led to the belief that NO may be involved in the regulation of autonomic outflow.There have been relatively few studies (8,19,20) that have examined specific sites within the forebrain involved in mediating the effect of NO on sympathetic nervous outflow. NOS is densely localized in the paraventricular nucleus (PVN) of the hypothalamus (1, 9, 14, 17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its effect here is once more to inhibit efferent sympathetic outflow by a mechanism that may be related to GABA. 59,60 Although there are some contrary results, 42,61-63 a picture emerges of NO acting as a neuromodulator within sites of central sympathetic neuronal integration to effect a tonic inhibition of central sympathetic outflow. This mechanism may be important in limiting sympathetic activation during stress as it has been observed that the number of NO producing neurons at key sites of autonomic processing in the brains of conscious rats increases in response to experimentally induced stress.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…These results indicate that Ang-II type 1 receptors within the PVN mediate an excitatory effect on RSND, AP, and HR, while NO in the PVN, which can be induced by ANG II stimulation, in turn inhibits the Ang-II-mediated increase in sympathetic nerve activity. This negative feedback mechanism within the PVN may play an important role in maintaining the overall balance and tone of sympathetic outflow [37][38][39] and suggests that Ang-II and NO interact with each other and regulate water and sodium intake and blood pressure by their central action, an action that is predominantly mediated by Angtype 1 (AT(1)) receptor. Subsequent studies revealed that Ang-II acts through G protein-coupled receptors of two pharmacological classes, AT(1) and AT(2), wherein AT(1) receptors, expressed in brain and peripheral tissues, mediate blood pressure homeostasis and regulation of drinking and water balance.…”
Section: Ras and Food Intakementioning
confidence: 99%